Epidemiologia da gestação múltipla: casuística de 15 anos - Rodrigues, CT (2012)
Between January of 1987 and December of 2001 were born 1243 twins related to 609 multiple pregnancies, in Maternidade Bissaya-Barreto. Data were grouped in periods of three years and several parameters were studied. The rate of multiple gestation has increased probably due to the contribution of the assisted conception techniques, and to the increase of the number of multiple fetal pregnancies (two or more) and to the increase of the mother age. These more frequent obstetric problems were preterm birth, gestational hypertension and abnormal sonographic data of fetal growth. The average age of delivery was 34 weeks and the birth weight has decreased. The most important factors for neonatal morbidity were hyaline membranous disease, intraventricular haemorrhage and the twin-twin transfusion syndrome. The neonatal mortality decreased in the last studied period.